Cigarette Smoke and Oxidative Stress - Halliwell, Barry B.; Poulsen, Henrik E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
From a public health point of view, there is little doubt that one of the most important preventable causes of disease worldwide is tobacco smoking. It is also clear that tobacco smoke contains a vast number of chemicals with important biological efects in disease processes. Te gas phase of tobacco smoke is oxidizing, the tar phase is reducing, and whole smoke is roughly neutral, so its efects on oxidative stress may be an “antioxidant paradox. ” From a scientifc point of view, we found it of interest to make a comprehensive ov- view of what we presently know about oxidative stress and tobacco smoke, because sm- ing is presently the best-known common condition associated with oxidative stress, and it may serve as a model for others. To this end, we have asked distinguished researchers from the public and the private sectors to evaluate the present scientifc status in their particular area. Authors were selected purely because of their scientifc merits. We do not claim that all the well-described health hazards associated with cigarette smoking stem from oxidative stress, nor should we. However, we ought to be able to fnd out, and for some of those health hazards, we can already say. We hope this book will stimulate more research to fnd answers to the remaining questions. Barry Halliwell and Henrik E. Poulsen Contents 1 Oxidative Stress . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 Barry B. Halliwell and Henrik E. Poulsen 2 Tobacco Smoke Constituents Affecting Oxidative Stress . . . . . . . . . . .
Oxidative Stress -- Tobacco Smoke Constituents Affecting Oxidative Stress -- Oxidative Modifications of Proteins and Lipids by Cigarette Smoke (CS). A Central Role for Unsaturated Aldehydes in CS-Mediated Airway Inflammation -- Cigarette Smoke-Induced Redox Signaling and Gene Expression in In Vitro and In Vivo Models -- Redox Effects of Cigarette Smoke in Lung Inflammation -- Oxidative Stress in the Pathogenesis of Chronic Obstructive Pulmonary Disease -- Modulation of Cigarette Smoke Effects by Diet and Antioxidants -- Modulation of Cigarette Smoke Effects by Antioxidants: Oxidative Stress and Degenerative Diseases -- Smoking Depletes Vitamin C: Should Smokers Be Recommended to Take Supplements? -- Experimental In Vitro Exposure Methods for Studying the Effects of Inhalable Compounds -- Oxidative Stress in Laboratory Animals Exposed to Cigarette Smoke, with Special Reference to Chronic Obstructive Pulmonary Disease -- Pulmonary Effects of Cigarette Smoke in Humans -- Smoking and Oxidative Stress: Vascular Damage -- Nrf2: a Transcription Factor that Modifies Susceptibility to Cigarette Smoke-Induced Pulmonary Oxidative Stress and Emphysema -- Tobacco Smoke and Skin Aging -- Cigarette Smoke and Oxidative DNA Modification.
Keywords: Oncology .; Respiratory organs—Diseases.; Medical biochemistry; Oncology; Pneumology/Respiratory System; Medical Biochemistry